Stakeholder Alignment Framework for Multinational Project Execution in Deepwater Petroleum Development Projects - Andrew Tochukwu Ofoedu; Joshua Emeka Ozor; Oludayo Sofoluwe; Dazok Donald Jambol (International Journal of Scientific Research in Civil Engineering, 2022)
Deepwater petroleum development projects are among the most complex and capital-intensive ventures in the energy sector, typically involving multinational stakeholders such as international oil companies (IOCs), national oil companies (NOCs), host governments, regulatory agencies, local communities, and global contractors. The diversity of interests, regulatory frameworks, cultural norms, and operational standards presents a significant challenge in achieving alignment across all stakeholders. Misalignment can lead to project delays, cost overruns, compliance violations, and reputational damage. This proposes a comprehensive Stakeholder Alignment Framework tailored specifically for multinational project execution in deepwater petroleum development. The framework addresses stakeholder identification and mapping, engagement strategies, governance structures, conflict resolution mechanisms, and performance monitoring. It incorporates tools such as power-interest matrices, RACI (Responsible, Accountable, Consulted, Informed) models, and digital collaboration platforms to facilitate transparent communication and joint decision-making. Special emphasis is placed on adaptive governance models that accommodate the dynamic nature of long-term deepwater projects and the need for iterative alignment as stakeholder priorities evolve. The framework also integrates cultural sensitivity and cross-border regulatory considerations, providing guidance on managing geopolitical risks and fostering local community relationships. By aligning stakeholder expectations and enhancing cooperative decision-making, the framework aims to mitigate risks and improve project outcomes in terms of cost efficiency, schedule adherence, and regulatory compliance. Case examples from recent deepwater developments in regions such as West Africa, South America, and Southeast Asia are used to illustrate the practical application and benefits of the framework. This contributes to the field of international project management in the oil and gas industry by offering a structured, adaptable approach to stakeholder alignment, which is critical for the success of multinational deepwater petroleum projects in increasingly complex global environments.